If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 41 + -4x = 2 + -6x + 4 Reorder the terms: 41 + 3x + -4x = 2 + -6x + 4 Combine like terms: 3x + -4x = -1x 41 + -1x = 2 + -6x + 4 Reorder the terms: 41 + -1x = 2 + 4 + -6x Combine like terms: 2 + 4 = 6 41 + -1x = 6 + -6x Solving 41 + -1x = 6 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 41 + -1x + 6x = 6 + -6x + 6x Combine like terms: -1x + 6x = 5x 41 + 5x = 6 + -6x + 6x Combine like terms: -6x + 6x = 0 41 + 5x = 6 + 0 41 + 5x = 6 Add '-41' to each side of the equation. 41 + -41 + 5x = 6 + -41 Combine like terms: 41 + -41 = 0 0 + 5x = 6 + -41 5x = 6 + -41 Combine like terms: 6 + -41 = -35 5x = -35 Divide each side by '5'. x = -7 Simplifying x = -7
| 30-(x+5)=8x-2 | | x(x+5)=2x+5 | | 15/h+35=95 | | 35+15/h=95 | | 5m^2-38m-16=0 | | 6+a=10 | | 12x-3=32x+12 | | x/5+5=305 | | A=3b+2 | | -1/2x=1048 | | 0.2+13=1.3-14.5 | | 6+3q=9+2q | | 13-37= | | 10x^2+10x-20=0 | | 2y-2=-6 | | 2y-3=-6 | | X+3=-x+12 | | 2(m-10)+2=24 | | (x+12)(x-2)=1 | | 2x+3=2y-7 | | 2x+6y=-12 | | 7(7-5x)=-38-6x | | x^2-6x-17= | | 9x^2-36+27=0 | | 4(w+8)=5(w-3) | | -4y-8x=8 | | 8m=3+5m | | -5+x=25 | | X^5-x^4-8x^3+12x^2=0 | | y=3600-.8y | | 3(2x^2+17x-9)=0 | | 64*3-3*9= |